1996
DOI: 10.2134/agronj1996.00021962003600060022x
|View full text |Cite
|
Sign up to set email alerts
|

Starter Fertilizer and Planting Date Effects on Corn Rotated with Cotton

Abstract: Corn (Zea mays L.) has become an important crop used in rotation with cotton (Gossypium hirsutum L.) in the mid‐South region of the USA, but there has been little research on cultural practices for corn in this cropping system. The objective of this study was to determine if starter fertilizer has beneficial effects on corn growth and grain yield at different planting dates. Starter fertilizer and planting date effects were evaluated for corn in field experiments on a Commerce silt loam (fine‐silty, mixed, non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 12 publications
6
29
1
Order By: Relevance
“…Tilled plots treated with starter fertilizer were 3.0 inches taller in both 2000 and 2001 than tilled plots with no starter fertilizer. Increased plant height caused by starter fertilizer has been documented in other studies (5,6,14,17). The three hybrids responded similarly to starter fertilizer with no interactions between starter fertilizer and hybrid.…”
Section: Plant Heightsupporting
confidence: 76%
See 2 more Smart Citations
“…Tilled plots treated with starter fertilizer were 3.0 inches taller in both 2000 and 2001 than tilled plots with no starter fertilizer. Increased plant height caused by starter fertilizer has been documented in other studies (5,6,14,17). The three hybrids responded similarly to starter fertilizer with no interactions between starter fertilizer and hybrid.…”
Section: Plant Heightsupporting
confidence: 76%
“…In 2001, plots treated with starter fertilizer reached R1 0.8 days earlier than plots with no starter fertilizer (Table 3). This response was much less than the 3‐to‐5‐day response from starter fertilizer observed by Mascagni and Bouquet (17) in Louisiana.…”
Section: Plant Developmentcontrasting
confidence: 55%
See 1 more Smart Citation
“…In contrast, seed weight was increased by enhancing overall corn plant growth at the seedling stage with starter fertilizer (Mascagni and Boquet 1996). However, increasing the amount of K fed to grain crops does not increase the K content of the seed to higher than 0.3% of the dry matter of the seed (Marschner 1986).…”
Section: Mineral Transport Into Seedmentioning
confidence: 99%
“…For example, researchers in Louisiana found that starter fertilizer increased corn yield regardless of hybrid or planting date, by increasing early-season plant height and reducing grain moisture and days to silking (Mascagni and Boquet 1996). In Missouri, Scharf (1999) found that corn yield increased by 800 kg ha 21 in a no-tillage (NT) situation, making starter fertilizer a profitable management tool.…”
Section: Introductionmentioning
confidence: 99%